Public Opinion of the Application of Sex Offender Notification Laws to Female Sex Offenders: Why It Is Important to Examine. (March 2017) - Cain, Calli M.; Sample, Lisa L.; Anderson, Amy L.
Sex offender notification laws depend not only on the public's access of registration information but also on the belief that those on the registry present a danger to society and thus deserve informal monitoring. As registries have expanded to include more people, perhaps citizens feel some people on registry are incapable of committing sex crimes or do not pose a danger to society. A group whose inclusion the public may question is women, as many scholars have argued there is a societal-level denial that females commit sex crimes. Data from the 2012 Nebraska Annual Social Indicators Survey were used to determine whether the public agreed that citizens should be notified of convicted female sex offenders living in their communities, whether they would take preventive action if a female sex offender lived in their neighborhood, and whether they think that female sex crimes are less serious than sex crimes committed by men.